Radiology’s role in dermatology: A closer look at two years of data - Tiryaki Baştuğ, Betül; Gencer Başol, Hatice (The European Research Journal, 2025)
Objectives: Radiological imaging plays a vital role in dermatology, addressing complex diagnostic needs beyond visual examination. The study focuses on the use of radiology services by the dermatology clinic at Bilecik Training and Research Hospital over two years (January 2023-December 2024), focusing on modality preferences, clinical indications, and diagnostic impact. Methods: Data from 451 imaging referrals were analyzed, covering patient demographics, imaging types, and clinical indications. Modalities included ultrasonography (USG), X-ray, magnetic resonance imaging (MRI), computed tomography (CT), and other specialized techniques. Trends and diagnostic yields were assessed, with subgroup analysis by age and gender. Results: Ultrasonography was the most frequently used imaging method (65.2%), followed by X-ray (18.6%), with MRI and CT used less often (5.1% and 4.4%, respectively). General medical examinations (29.93%) were the leading indication, achieving the highest diagnostic yield (85%). Pruritus (9.31%) and psoriasis (7.76%) were also notable indications. Most referrals involved middle-aged (41-60 years) and older adults (61+ years). Conclusions: Ultrasonography and X-ray remain foundational tools in dermatology, providing essential support for diagnosis and management. These findings highlight the need for resource optimization and stronger collaboration between dermatology and radiology. Future research should explore imaging outcomes and emerging technologies to advance dermatological care.